Comparison between univariate and bivariate geostatistical models for estimating catch per unit of effort (cpue): A simulation study - Pereira, Julio Cesar; Leandro, Roseli Aparecida; Petrere, Miguel [UNESP]; Nishida, Tom (Elsevier B.V., 2012)
Data on catch and fishing effort are used for estimating the relative abundance of a fish stock. Geostatistical models have been used in this sort of analysis. Multivariate geostatistical models have been used in several areas but not often with fisheries data. In this paper a simulation study was carried out in order to compare an index of catch per unit of fishing effort (cpue) based on: (1) the adjustment of a univariate geostatistical model of the ratio between catch and effort; and (2) a bivariate model in which catch and effort are simultaneously modeled. The estimates obtained from both models presented close results suggesting that there is no advantage in using the bivariate model for estimating the index and indicating that the univariate model is preferred. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Bayesian inference; Geostatistical models; Cpue; Simulation